2015
DOI: 10.1021/jacs.5b03579
|View full text |Cite
|
Sign up to set email alerts
|

Combined CO2-philicity and Ordered Mesoporosity for Highly Selective CO2 Capture at High Temperatures

Abstract: Various dry sorbents have been lately introduced as promising media to capture carbon dioxide (CO2). However, it is still desirable to further improve their performance in diverse aspects, and high temperature selectivity of CO2 over other gases is clearly one of them. Here, we report a co-assembly approach to turn nonporous melamine resin to a highly ordered mesoporous polymeric network (space group: Im3̅m) containing high nitrogen content (∼18 at%). This mesoporous network shows anomalously increasing CO2/N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 70 publications
3
95
0
1
Order By: Relevance
“…Similar temperature dependencies were previously reported for a CO 2 -philic mesoporous phenolic-functionalized melamine resin 30 and N 2 -phobic nitrogen-rich azo-covalent organic polymers. 31 In addition, the ideal adsorption solution theory (IAST) selectivity (assuming 0.1/0.9 mixture of CO 2 /N 2 at 1 bar) was found to be 27:1, 39:1 and 139:1 at 273 K, 298 K and 323 K, respectively (see Supporting Information).…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 86%
“…Similar temperature dependencies were previously reported for a CO 2 -philic mesoporous phenolic-functionalized melamine resin 30 and N 2 -phobic nitrogen-rich azo-covalent organic polymers. 31 In addition, the ideal adsorption solution theory (IAST) selectivity (assuming 0.1/0.9 mixture of CO 2 /N 2 at 1 bar) was found to be 27:1, 39:1 and 139:1 at 273 K, 298 K and 323 K, respectively (see Supporting Information).…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 86%
“…In recent years, many amine functionalized or nitrogen-rich porous materials were found to show good CO 2 adsorption properties because of the existence of strong interactions between the nitrogen functionality and CO 2 molecules [21][22][23][24][25][26][27]. Among them, the porous melamine-formaldehyde resins (PMFRs) have gained great attention because they can be produced by low-cost highly abundant melamine that has suitable alkalescence (pKa = 5.5) versatile reactivity [28][29][30]. In addition, it is a mass produced product in the chemical industry and can be used as crosslinker in organic coating and plastic [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the PMFRs can be synthesized by using the microemulsion approach or the template method, such as SiO 2 particles [34]. However, PMFRs produced by these approaches normally have a low BrunauerEmmett-Teller (BET) specific surface area, which were listed in Table 1 [28,31]. When used for CO 2 adsorption, their capacity is typically not exceeding 1.6 mmol/g (273 K, CO 2 partial pressure 0.03).…”
Section: Introductionmentioning
confidence: 99%
“…50 It also demonstrates that the azo-modification of pore surface is promising in improving overall performance in carbon dioxide adsorption. 52,53 Choi demonstrated that the N 2phobicity of porous polymers, of which the N 2 uptake capacity decreases significantly with an increasing adsorption temperature, is most possibly scripted to the relatively large portion of mesoporosity. For comparison, two calculating models, such as initial slope method (IS) estimated from Henry's law constants 51 and the ideal adsorbed solution theory (IAST) 31 were applied to probe the idea selectivity.…”
Section: Resultsmentioning
confidence: 99%